Physical Development of Schoolchildren Residing in the Southern Regions of the Kyrgyz Republic - Feruza A. Kochkorova; Raisa M. Atambaeva; Gulzhan S. Kitarova (Педиатрическая фармакология, 2018)
The physical development (FR) of children is one of the main criteria for the health status of the child population, reflecting the effect on the body of endogenous and exogenous factors. The purpose of the study is to study the physical development of schoolchildren living in the southern regions of the Kyrgyz Republic. Methods. Measurements of growth, weight, and circumference of the thorax were taken in urban and rural schoolchildren residing in the southern regions of the Kyrgyz Republic. The study period was from October 2015 to January 2017. Results. According to the results of the studies, the smallest increases in length and body weight were observed between the ages of 7 and 8 in schoolchildren of both sexes. The rate of weight gain was from 1.0 to 1.2 kg and growth was from 3.0 to 3.3 cm. The greatest difference in the growth rate among schoolchildren was found at the age of 11 and 12 (p<0.001), in girls at the age of 11, 12 and 16 years of age (p<0.001). The annual average increase in body length at the age of 7–17 in urban and rural boys was 4.4 and 2.9 cm, respectively, in girls — 2.8 and 27 cm. The growth retardation of boys was observed at 17 years with a growth rate of 1.3%, and in girls aged 15 years — 1.8%. The greatest increase in weight in urban schoolchildren of both sexes was observed between the ages of 10 and 11 (5.6%), and in rural aged 12–13 years (5.3%). The annual average increase in the chest circumference at the age of 7–17 years in urban schoolchildren was 2.5 cm, in girls — 2.2 cm, and in rural schoolchildren this indicator was at the level of 2.0 and 2.1 cm, respectively. The conclusion. The studied data of anthropometric indicators was used in the development of standards for the physical development of urban and rural children (7–17 years) of school age in the southern region of the Kyrgyz Republic, and their physical development was assessed.